Defining and assessing adverse environmental impact from power plant impingement and entrainment of aquatic organisms - Dixon, Douglas A.; Veil, John A.; Wisniewski, Joe (A.A. Balkema Publishers, 2003)
A collection of technical papers assessing the effects of power plant water intake on the aquatic environment. Papers present various stakeholder views on the meaning of "adverse environmental impact" under Section 316(b) of the US Clean Water Act.
Symposium held in conjunction with the Annual Meeting of the American Fisheries Society, Aug. 23rd 2001 in Phoenix, Arizona.
Keywords: Electric power-plants -- Waste disposal -- Environmental aspects -- Congresses.; Electric power-plants -- Water-supply -- Congresses.; Water quality management -- Congresses.; Aquatic organisms -- Effect of water pollution on -- Congresses.; elektronické knihy; electronic books